Assessment of marine benthic diatom communities: insights from a combined morphological–metabarcoding approach in Mediterranean shallow coastal waters. (January 2022) - Pérez-Burillo, Javier; Valoti, Greta; Witkowski, Andrzej; Prado, Patricia; Mann, David G.; Trobajo, Rosa
Abstract: We investigated the advantages and disadvantages of light microscope (LM)-based identifications and DNA metabarcoding, based on a 312-bp rbcL marker, for examining benthic diatom communities from Mediterranean shallow coastal environments. For this, we used biofilm samples collected from different substrata in the Ebro delta bays. We show that 1) Ebro delta bays harbour high-diversity diatom communities [LM identified 249 taxa] and 2) DNA metabarcoding effectively reflects this diversity at genus- but not species level, because of the incompleteness of the DNA reference library. Nevertheless, DNA metabarcoding offers new opportunities for detecting small, delicate and rare diatom species missed by LM and diatoms that lack silica frustules. The primers used, though designed for diatoms, successfully amplified rarely reported members of other stramenopile groups. Combining LM and DNA approaches offers stronger support for ecological studies of benthic microalgal communities in shallow coastal environments than using either approach on its own. Graphical abstract: Unlabelled Image Highlights: Ebro Delta bays harbour very rich diatom communities. DNA metabarcoding is an efficient tool for studying diatom diversity at genus level DNA metabarcoding detects delicate, small and rare species missed by LM. A major discrepancy between methods is perhaps explained by endosymbiosis or kleptoplasty Primers designed for diatoms amplify some important non-diatom species.